Rhetorical Structure of Introduction in Applied Linguistics Research Articles - Rahman, Mizanur; Darus, Saadiyah; Amir, Zaini (EDUCARE, 2017)
ABSTRACT: The RA (Research Article) is considered to be the main channel of knowledge production. However, for student writers and novice scholars writing, RA is a challenging task. It is partly because of lack of exposure to and awareness of the rhetorical structure of RAs (Research Articles) in the intended discipline. The objective of this study is to identify the rhetorical moves of RAs in applied linguistics and explaining their communicative functions that can be used for pedagogic purposes for novice scholars in this discipline. Analyses of moves and their constituent steps together with their frequency count would help suggest obligatory and optional moves in the Introduction section. Also analysis of move structural patterns, which would enable to draw possible move sequencing is within the purview of this study. A corpus of 20 empirical RAs of leading and representative 4 journals in applied linguistics have been analyzed following J.M. Swales (1990 and 2004) move analysis of Introduction sections of empirical RAs. Results were obtained through software coding of moves of these 20 RAs, and through qualitative analysis of communicative functions of moves and steps. From the frequency count of moves and steps, it is found that some moves and their constituent steps are obligatory, while others are optional. Findings show they both conform to and depart from J.M. Swalesâ CARS (Create-a-Research-Space) model in 1990 and 2004. The findings of the study will facilitate better understanding of RAs in applied linguistics for novice scholars and contribute to these scholarsâ efforts to publish their research in this field.KEY WORDS: Introductions; Research Articles; Rhetorical Structure; Move Analysis; Genre.Â Â Â Â About the Authors: Mizanur Rahman is a Ph.D. Candidate in English Language Studies at the UKM (National University of Malaysia); and also an Assistant Professor at the Department of Humanities BUET (Bangladesh University of Engineering and Technology) in Dhaka 1000, Bangladesh. Assoc. Prof. Dr. Saadiyah Darus and Assoc. Prof. Dr. Zaini Amir are the Lecturers at the School of Language Studies and Linguistics, Faculty of Social Sciences and Humanities UKM, 43600 UKM Bangi, Selangor, Malaysia. For academic interests, the authors can be contacted via e-mail at: m.rahman.1978@gmail.comHow to cite this article? Rahman, Mizanur, Saadiyah Darus & Zaini Amir. (2017). âRhetorical Structure of Introduction in Applied Linguistics Research Articlesâ in EDUCARE: International Journal for Educational Studies, Vol.9(2), February, pp.69-84. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-7877. Chronicle of the article: Accepted (September 27, 2016); Revised (January 27, 2017); and Published (February 27, 2017).